Physical performance of elite and subelite Spanish female futsal players - DJ Ramos-Campo; JA Rubio-Arias; M Carrasco-Poyatos; PE Alcaraz (Termedia Publishing House, 2016)
The aim of this study was to determine the parameters distinguishing top female futsal players from lower level players. Twenty-seven female futsal players participated in the study, composed of professional first division (elite; n=15) players and semi-professional second division players (sub-elite; n=14). Active and passive straight leg raise tests, isokinetic strength of the knee extensor and flexor muscles at 60º • s-1 angular velocity, squat and counter movement jumps, 30 m sprint, 30 m agility, repeated sprint ability test and maximum ball speed during shooting were measured. The elite players were more agile and kicked harder than sub-elite players in maximum ball speed during the shooting test (P≤0.05). However, no significant differences between teams were observed in active and passive hamstring flexibility, jumping ability, repeated sprint ability test, 30 m sprint time, H/Q ratio and absolute and relative torque from 60° • s-1 angular velocity. Based on these findings we conclude that agility and maximum ball speed during shooting may be important determinant factors of Spanish female futsal actions and could distinguish ability at high-level games.